(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The development of self-development skills among future teachers is critical to ensure they become lifelong learners and effective educators in a rapidly changing educational landscape. This article explores the importance of fostering these skills during teacher education programs, emphasizing theoretical perspectives and practical methods for integrating these competencies into teacher training. Highlighting effective strategies and practical applications, the article underscores self-development as an integral part of professional growth for future educators.